2017
DOI: 10.1038/nature24268
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proofreading governs CRISPR–Cas9 targeting accuracy

Abstract: The RNA-guided CRISPR-Cas9 nuclease from Streptococcus pyogenes (SpCas9) has been widely repurposed for genome editing1–4. High-fidelity (SpCas9-HF1) and enhanced specificity (eSpCas9(1.1)) variants exhibit substantially reduced off-target cleavage in human cells, but the mechanism of target discrimination and the potential to further improve fidelity were unknown5–9. Using single-molecule Förster resonance energy transfer (smFRET) experiments, we show that both SpCas9-HF1 and eSpCas9(1.1) are trapped in an in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
877
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 971 publications
(974 citation statements)
references
References 29 publications
51
877
1
1
Order By: Relevance
“…moved FRET efficiency to the HNH inactive state [16]. Similar effects were also observed with eSpCas9(1.1) variants.…”
Section: Improved On-target Specificity Of Crispr-cas9 and Cpf1 Endonsupporting
confidence: 66%
See 2 more Smart Citations
“…moved FRET efficiency to the HNH inactive state [16]. Similar effects were also observed with eSpCas9(1.1) variants.…”
Section: Improved On-target Specificity Of Crispr-cas9 and Cpf1 Endonsupporting
confidence: 66%
“…The specificity of high-fidelity SpCas9 enzyme was enhanced further by additional mutation D1135E, and two mutations for hydrophobic or stacking interaction of residues L169A and Y450A that interacts with the 5th and 7th PAM proximal nucleotides, respectively [15]. Essentially the same dissociation constants were observed with wild type enzyme, and high fidelity variants eSpCas9(1.1) and SpCas9-hf1 [16].…”
Section: Improved On-target Specificity Of Crispr-cas9 and Cpf1 Endonsupporting
confidence: 60%
See 1 more Smart Citation
“…However, while CRISPR struggles as a standalone therapy, several efforts to minimize off-target cleavage have been reported. Recently, the development of an improved Cas9 variant with enhanced proofreading capacities has extensively reduced off-targeting effects while maintaining the high-cutting efficiency [9]. Additionally, powerful molecules with the ability to inactivate Cas proteins activity, named anti-CRISPR proteins, have been reported to significantly reduce off-targeting edits [89].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While there is concern for off-target effects, in other words, mutations occurring at sites other than the target gene, so far the proof-of-concept studies have found little evidence of this phenomenon in vivo, although the currently used techniques are not sensitive enough to detect mutations occurring in less than one in 10,000 cells. Furthermore, serial innovations with CRISPR-Cas9 are progressively reducing its risk of off-target effects [9][10][11]. Importantly, CRISPR-Cas9 has proven effective in targeting human PCSK9 in authentic human hepatocytes in vivo in a liver-humanized mouse model, suggesting that PCSK9-targeting genome-editing therapies would be similarly effective in live humans [7].…”
Section: Somatic Therapymentioning
confidence: 99%